Progress report on the adoption of the Rights Retention Strategy (RRS) - De-Castro, Pablo (Anuario ThinkEPI, 2024)
Two years after the publication of the original ThinkEPI note on the topic of the RRS –“The Plan S Rights Retention Strategy: Are we witnessing the end of embargo periods?”– it seems a good moment to take stock and examine the progress in the application of this embargo-free Green Open Access route. 35 UK universities – most of them research-intensive institutions – have passed their Institutional Rights Retention Policy (IRRP) at the time of writing. This piece examines the advances in the application of these policies and offers some results for the uptake of the IRRP at the author’s own institution.
Keywords: Open access; Green route; Embargo periods; Rights Retention Strategy (RRS); Institutional Rights Retention Policy (IRRP); Scholarly communication